2016
DOI: 10.1002/mabi.201600074
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Surface of Nanoparticles: Impact of Poly(2‐ethyl‐2‐oxazoline) on Protein Adsorption in Serum and Cellular Uptake

Abstract: Due to the adsorption of biomolecules, the control of the biodistribution of nanoparticles is still one of the major challenges of nanomedicine. Poly(2-ethyl-2-oxazoline) (PEtOx) for surface modification of nanoparticles is applied and both protein adsorption and cellular uptake of PEtOxylated nanoparticles versus nanoparticles coated with poly(ethylene glycol) (PEG) and non-coated positively and negatively charged nanoparticles are compared. Therefore, fluorescent poly(organosiloxane) nanoparticles of 15 nm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 78 publications
(75 reference statements)
1
35
1
3
Order By: Relevance
“…Although this group did not perform circulation studies they did investigate their nanogels for induced hemolysis and erythrocyte aggregation and found no significant interaction of the nanogels with blood. Other recent studies on PEtOx modified nanoparticles and PMeOx coated viruses, each without the ability to vary the zeta potential, similarly found reduced interaction of PAOx modified materials with cells.…”
Section: Emerging Applicationsmentioning
confidence: 71%
“…Although this group did not perform circulation studies they did investigate their nanogels for induced hemolysis and erythrocyte aggregation and found no significant interaction of the nanogels with blood. Other recent studies on PEtOx modified nanoparticles and PMeOx coated viruses, each without the ability to vary the zeta potential, similarly found reduced interaction of PAOx modified materials with cells.…”
Section: Emerging Applicationsmentioning
confidence: 71%
“…68,69 Recent work has suggested that poly(2-methyl-2-oxazoline) has similar protein repellent features to poly(ethylene oxide). [70][71][72] Poly(2-oxazoline)s (POx) are synthesized through a controlled, living polymerization, facilitating tunable block structure, length, and selective comonomer addition. 73,74 Based on these collective attributes, we focused on amphiphilic poly(2-oxazoline) surfactants to decouple the physiochemical properties of nanoemulsions and facilely control their surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] As highlighted by Maskos and co-workers even absolute particle sizes can be calculated from the retention times by calibrating the system with standard-size particles. [42] However,u pt ov ery recently AF4 was not commonly adopted to separate free proteins from nanocarrier-protein complexes for further corona analysis.In summary,the above-mentioned works have exploited AF4 as an analytical method to evaluate the change of retention time due to size increase,b ut not as as eparation tool for further protein corona analysis with ex situ measurements.…”
Section: Protein Corona Isolation Based On Chromatographic Methodsmentioning
confidence: 99%